A 2, 3‐butanediol dehydrogenase from Paenibacillus polymyxa ZJ‐9 for mainly producing R, R‐2, 3‐butanediol: Purification, characterization and cloning. (7th September 2012) - Gao, Jian; Yang, Huan‐Huan; Feng, Xiao‐Hai; Li, Sha; Xu, Hong
<x xml:space="preserve">Abstract</x> A 2, 3‐butanediol dehydrogenase (BDH) from Paenibacillus polymyxa ZJ‐9 was purified to homogeneity via fractional ammonium sulfate precipitation, followed by two steps of anion‐exchange chromatography using DEAE‐Sepharose and Source 15Q, obtaining a 35‐fold increase in specific activity and 34.9% yield. The molecular weights of the purified BDH subunit and holoenzyme were 44.5 and 90.0 kDa, respectively, as detected via SDS‐PAGE and gel filtration chromatography. These results were significantly different from those of other reported BDHs. Substrate specificity experiments showed that the enzyme could function preferentially as a reductase rather than as a dehydrogenase, and was mainly responsible for the reduction of R‐acetoin to R, R‐2, 3‐butanediol. Gene cloning, sequencing, and expression experiments further demonstrate that this enzyme was a new type of BDH.